REPRESENTASI BUDAYA PATRIARKI DI KOREA SELATAN DALAM FILM KIM JI YOUNG BORN 1982 - Sasqia Dinda Riyadi; Nurul Fauziah (Kinesik, 2022)
The film Kim Ji Young Born 1982 presents a portrait story of the patriarchal society in South Korea. Even so, the social life of South Korean society itself is still very conservative. The film Kim Ji Young Born 1982 contrasts the impact of patriarchal culture on women's rights in their lives. Also, the burden of women's lives in a patriarchal and conservative society in every choice of life. Using a qualitative approach with John Fiske's semiotic analysis as a research method, this study aims to uncover the 1982 film Kim Ji Young Born through the representation of patriarchal culture in South Korea, by examining the signs and meanings in this film. The result of the research shows that there are 16 film scenes that depict patriarchal culture through the level of reality, the level of representation, and the level of ideology. The patriarchal culture in this film is depicted in six indicators of the basic structure of patriarchy, namely the patriarchal mode of production, patriarchal relations in paid work, male violence, patriarchal relations in sexuality, patriarchy in cultural institutions and the patriarchal state. Unfortunately, the scenes that show various patriarchal cultural practices are done consciously or unconsciously by the people around the main character.